3-Nitropropionic acid production by the endophytic Diaporthe citri: Molecular taxonomy, chemical characterization, and quantification under pH variation. Issue 12 (December 2016) - Polonio, Julio Cesar; Ribeiro, Marcos Alessandro dos Santos; Rhoden, Sandro Augusto; Sarragiotto, Maria Helena; Azevedo, João Lúcio; Pamphile, João Alencar
Abstract: 3-nitropropionic acid (3-NPA) is a nitrogenated compound produced by plants and fungi and has been associated with poisoning episodes in humans, animals, and to induction of Huntington disease symptoms in rats. The production of 3-NPA by endophytes has been reported, but the function and biosynthesis are not well-defined. The specie of endophytic strain G-01 was confirmed as Diaporthe citri using a multilocus sequence analysis, and was verified different concentrations of 3-NPA produced at different initial pHs by these strain. The chemical analysis indicated that 3-NPA was the majority compound present in the crude extracts. The better extraction condition was at an initial pH of 7.0 for 22 d, yielding about 80 % of 3-NPA per mg of extract. It was observed that the concentration of 3-NPA increased after the initial consumption of reduction sugars, indicating that the compound is produced after the high energetic production phase of the fungus. These and other studies demonstrate the production of this compound by plants and endophytic fungi, indicating that 3-NPA may be involved in defence and nutrition systems of endophytes and host plants, and they also might participate in the biogeochemical nitrogen cycle. Highlights: High concentration of 3-NPA-producing by endophyte Diaporthe citri . pH affecting the 3-nitropropionic acid-producing. Endophytes-plant interaction correlated with 3-Nitropropionic acid.